2017
DOI: 10.1111/jcpe.12840
|View full text |Cite
|
Sign up to set email alerts
|

Levels of serum retinol‐binding protein 4 before and after non‐surgical periodontal treatment in lean and obese subjects: An interventional study

Abstract: RBP4 was associated with chronic periodontitis before and after non-surgical periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 38 publications
(53 reference statements)
4
42
0
Order By: Relevance
“…In this line, other inflammatory molecules, including TNFα (Nishimura et al., ; Gonçalves et al., ) and RBP4 (Martinez‐Herrera et al., ), have generally been found to be higher in periodontitis patients than in healthy controls and have been related with atherosclerosis. It has been shown that TNFα activates endothelial cells at the site of inflammation, leading to oxidative stress via escalating ROS production by endothelial cells (Yan et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…In this line, other inflammatory molecules, including TNFα (Nishimura et al., ; Gonçalves et al., ) and RBP4 (Martinez‐Herrera et al., ), have generally been found to be higher in periodontitis patients than in healthy controls and have been related with atherosclerosis. It has been shown that TNFα activates endothelial cells at the site of inflammation, leading to oxidative stress via escalating ROS production by endothelial cells (Yan et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has suggested that obesity plays a negative role in the response to non‐surgical periodontal therapy (Suvan et al., ; Bouaziz et al., ; Gonçalves, Feres, et al., ; Gonçalves, Zimmermann, et al., ; Martinez‐Herrera et al., ). However, to date, few studies have evaluated the beneficial effect of weight loss on chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In reference to sample size determination, the present study was designed to have a power of 80% in order to be able to detect differences of ≥0.15 between the groups in relation to the primary efficacy criterion (absolute PD variation), assuming a common standard deviation of 0.21. This was based on data obtained in a previous study by our group (Martinez‐Herrera et al., ) and a dropout rate of 33% among obese patients submitted to dietary therapy. Under these premises, at least 46 subjects per group were considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of RBP4 did not differ between groups, and no statistically noticeable changes after periodontal therapy could be observed. However, a recent interventional case–control study reported decreasing serum concentrations of RBP4 at 12 weeks after non‐surgical periodontal treatment in lean and obese patients (Martinez‐Herrera et al, 2018). However, we could not confirm these results for our 27.5‐months observation and treatment period.…”
Section: Discussionmentioning
confidence: 99%